EKSPLORASI ETNOMATEMATIKA PADA ALAME DAN KIPANG SEBAGAI MAKANAN KHAS MANDAILING - Nurafnizar Nasution; Rusi Ulfa Hasanah (EMTEKA: Jurnal Pendidikan Matematika, 2023)
Alame and kipang Panyabungan are typical Mandailing foods. Alame and kipang Panyabungan are quite popular among the people of North Sumatra until now. This study aims to explore mathematical concepts that are in the alame and kipang Panyabungan so that they can be known and used in mathematics subject matter. This research uses a qualitative method of exploration through an ethnographic approach with primary data collection techniques in the form of observations, interviews, documentation and secondary data by conducting literature studies conducted by researchers. The data analysis technique used in this study is descriptive analysis, namely data reduction, data presentation and drawing conclusions. The results showed that there is mathematical knowledge such as counting, unit elements, measurements, angles, comparisons, flat buildings, building spaces, and social arithmetic.